Does sildenafil have protective effects against ovarian ischemia-reperfusion injury in rats? - (:unkn) unknown (SPRINGER HEIDELBERG, 2015)
The aim of this study was to evaluate the protective activity of sildenafil treatment against ischemia-reperfusion damage created experimentally in rat ovaries. For this study, 42 female Wistar rats were used, and the rats were separated randomly into six groups consisting of seven rats each: sham, torsion, torsion-detorsion, torsion-detorsion + saline, torsion-detorsion + sildenafil 0.7 mg/kg and torsion-detorsion + sildenafil 1.4 mg/kg. With the exception of the sham group, an ovarian torsion procedure was implemented in all other groups for 2 h. Then, a detorsion procedure was implemented to the groups for 2 h, with the exception of the torsion group. Medications were given intraperitoneally, one-half hour before the detorsion procedure in the saline, 0.7 and 1.4 mg/kg sildenafil groups. Finally, 2 ml of blood samples was drawn for markers of oxidative stress, while the ovaries which were torsioned for the histological examination were extracted from all rats. According to the histopathological damage scores, the least damage was seen in the sham group and the most damage was seen in the torsion-detorsion group. The sildenafil treatment appeared to be effective in decreasing tissue damage; however, there were no differences between the dosages. Additionally, it was determined that the oxidative stress levels were higher in the torsion-detorsion group, while the sildenafil treatment caused a significant decrease in the oxidative stress levels. The results of the current study showed that the sildenafil treatment can be effective in preventing tissue damage and oxidative stress induced by the ischemia-reperfusion created in rat ovaries.
Keywords: Adnexal torsion; Ischemia-reperfusion injury; Sildenafil; Rat model; ERYTHROPOIETIN; CITRATE; DAMAGE; MODEL